Modelling for The Risk Factors Early Introduction to Complementary Food for A Baby Under Six Months Old in the Working Area of Kambaniru Public Health Center in East Sumba Districts - Heru Syaputra Gotlief Lutang; Jacob M Ratu; Noorce Ch Berek (Humanistic Network for Science and Technology (HNST), 2020)
Complementary foods are foods/drinks that were given to complement breastfeeding in order to fulfil the nutritional of baby from 6-24 months old. However, have been given to several babies under six months which may increase the mortality risk. Early introduction of complementary foods to the baby are influenced by factors education, occupation, income, tradition, myths, familial support, and knowledge. This study aims to analyze the factors that resulted in the early introduction to complementary foods in the working area of Kambaniru Public Health Center. This was an observational analytic study with cross sectional design. The samples were 89 mothers. Partial correlation between the risk factor was analyzed using the simple logistic regression test, while the modelling for the risk factors was analyzed using the multiple logistic regression test. The result showed that there were 51.7% of the mothers that gave an early complementary foods to the babies, there was a correlation between knowledge (p=0.000), income (p=0.026), myths (p=0.016) and familial support (p=0.000), while education (p=0.089), occupation (p=0.0307) and tradition (p=0.374) did not correlate. The conclusion of this study was that familial support and knowledge factors were the models to predict the early introduction to complementary food with 44.2% contributing factors. Keywords: complementary foods; familial support; knowledge; myths; tradition